Design and Development of Ground Based Radar Systems for Vegetation Studies - Lim, Ka Sing (2009)
In this research work, two ground-based radar systems have been developed namely the near real-time automated C-band scatterometer system (NRT-SCATT) and the wideband VNA ground-based radar system with real and synthetic aperture radar (WRSAR). They have been constructed to surmount the challenges and provide alternative solution to the existing systems.